Banks at risk : global best practices in an age of turbulence - Hoflich, Peter (John Wiley & Sons(Asia), 2011)
Although risk management is acknowledged as an important area of expertise in any bank, it is often held hostage by the business side whenever a bottom line is involved-which is nearly always. With banks all over the world in crisis, most often caused by over-ambitious and imprudent business leaders, risk management is returning to the fore